2015
DOI: 10.1007/s10600-015-1399-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Sulfobetaines Based on Betulinic Acid and its Esters

Abstract: Methods for preparing sulfobetaines of betulinic acid that contained N,N-(dimethylammonium)butane-1-sulfonate, a new type of Zwitter-ion in a series of lupane-type pentacyclic triterpenoids, were developed in order to prepare new betulinic acid derivatives and to study the structure-biological-activity relationship.Keywords: betulinic acid, 1,4-butane sultone, sulfobetaine.Betulinic acid is the lead compound among lupane-type pentacyclic triterpenoids and is interesting as a platform for developing drugs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Positions 3 and 28 of BA skeleton are easily functionalized through esterification reactions and, consequently, many studies involving this transformation have been reported [17,22,27,31,34,35,36,37,38,39,40,41,42,43,44,45,46,47]. The used methodologies involve: (i) The reaction of 17-COOH group of BA 1 with alkyl halides in the presence of a base (mainly, K 2 CO 3 ), or (ii) the reaction of BA-based acyl chloride intermediate with alcohols, or even (iii) the reaction of 3-OH group of BA 1 with acid anhydrides in the presence of a catalyst [usually, 4-(dimethylamino)pyridine (DMAP)] (Scheme 11).…”
Section: Simple Transformationsmentioning
confidence: 99%
“…Positions 3 and 28 of BA skeleton are easily functionalized through esterification reactions and, consequently, many studies involving this transformation have been reported [17,22,27,31,34,35,36,37,38,39,40,41,42,43,44,45,46,47]. The used methodologies involve: (i) The reaction of 17-COOH group of BA 1 with alkyl halides in the presence of a base (mainly, K 2 CO 3 ), or (ii) the reaction of BA-based acyl chloride intermediate with alcohols, or even (iii) the reaction of 3-OH group of BA 1 with acid anhydrides in the presence of a catalyst [usually, 4-(dimethylamino)pyridine (DMAP)] (Scheme 11).…”
Section: Simple Transformationsmentioning
confidence: 99%